This thing called the world : the contemporary novel as global form - Ganguly, Debjani (Duke University Press, 2016)
Debjani Ganguly theorizes the contemporary global novel and the social and historical conditions that shaped it, showing how in 1989 the consolidation of the information age, the perpetual state of war, and the focus on humanitarianism transformed the novel into a form that addresses contemporary social, technological, and political upheavals.